فاعلية استراتيجية العصف الذهني في تنمية التحصيل الدراسي لدى طالبات الصف الثاني المتوسط بمدينة الرياض المملكة العربية السعودية في مادة الدراسات الاجتماعية والوطنية - القحطاني، شاهرة بنت سعيد محي (جامعة مؤتة, 2018)
The study aimed at identifying the effectiveness of brainstorming strategy in the academic achievement of Second grade students intermediate. Riyadh، Saudi Arabia، social and national studies The researcher used the semi-experimental method in addition to measuring pre and post variables to the study. The Research was conducted on the second grade intermediate students. They were 22417 students. The research sample included two classrooms of the second grade students at Second-Year Intermediate the Intermediate School (100) in Riyadh, which has been randomly selected. The represented sample was divided into two group, the sample consists of (60)students. (30) students were as experimental sample, (30) students were as control sample. The research results, there are a statistically significant differences at the level of significance (0.01), for the experimental sample which were taught according to the brainstorming strategy. That indicates the effectiveness of this strategy in improving the students' academic achievement. According to these results, the study made some recommendations such as: - It's necessary for the teachers to use brainstorming strategy for its effective role in improving the students' levels. - Forming educational preparation programs that contain the modern teaching methods for their positive effect on the learners.
هدفت الدراسة إلى التعرف على فاعلية استراتيجية العصف الذهني على تحصيل طالبات الصف الثاني المتوسط بمدينة الرياض - المملكة العربية السعودية في مادة الدراسات الاجتماعية والوطنية وقد استخدمت الباحثة المنهج شبه التجريبي بالإضافة للقياس القبلي والبعدي لمتغيرات الدراسة. وتمثل مجتمع البحث طالبات الصف الثاني المتوسط بمدينة الرياض والبالغ عددهن 22417 طالبة، بينما تمثلت مجموعة البحث صفان من فصول الصف الثاني المتوسط بالمتوسطة المائة بمدينة الرياض التي تم اختيارها بطريقة عشوائية، وتتكون العينة من (60) طالبة منهن (30) طالبة يمثلن مجموعة تجريبية، و(30) طالبة يمثلن مجموعة ضابطة. وقد توصلت الدراسة إلى وجود فروق ذي دلالة إحصائية عند مستوى دلالة (0.01) لصالح المجموعة التجريبية التي درست باستراتيجية العصف الذهني. وبهذه النتيجة يستدل أن لاستراتيجية العصف الذهني تأثيراً فاعلاً في تحسين مستوى التحصيل الدراسي لدي تلك الطالبات. وفي ضوء النتائج السابقة خرجت الدراسة بتوصيات من أبرزها، ضرورة توجيه المعلمات لاستخدام استراتيجية العصف الذهني لدورها الفاعل في رفع مستوى التحصيل لدى المتعلمات، كذلك تضمين برامج الإعداد التربوي بكليات التربية مقررات طرائق التدريس الحديثة لتأثيرها الإيجابي على المتعلم.
Keywords: السعودية -- التعليم المتوسط -- طرق التدريس -- استرايجية العصف الذهني -- الدراسات الاجتماعية -- التحصيل الدراسي